Devitrification of thin film Cu-Zr metallic glass via ultrashort pulsed laser annealing - Antonowicz, Jerzy; Zalden, P.; Sokolowski-Tinten, K.; Georgarakis, Konstantinos; Minikayev, R.; Pietnoczka, A.; Bertram, F.; Chaika, M.; Chojnacki, M.; Dłużewski, P.; Fronc, K.; Greer, A. Lindsay; et al. (Elsevier, 2021)
In this work we report on an ultrashort pulsed laser annealing-driven devitrification of thin film Cu67Zr33 metallic glass characterized by micro-beam X-ray diffraction and electron microscopy techniques. The essential feature of ultrashort pulsed laser annealing is ultrafast heating (1014 K/s) by femtosecond optical excitation followed by extremely rapid cooling (1010–12 K/s) due to heat dissipation into the film substrate. During repetitive optical excitation, we take X-ray diffraction snapshots of the intermediate, frozen-in stages of the glass-crystal transformation to study its kinetics. A quantitative analysis of the diffraction patterns supported by electron microscopy result shows that the glass-crystal transformation proceeds by a rapid formation of an energetically favourable layer of crystalline ZrO2 on the free surface of the glassy film accompanied by nucleation and growth of fcc-Cu in the residual amorphous matrix. We demonstrate that at low effective annealing temperatures the devitrification kinetics of both products is correlated, while at high temperatures they decouple and ZrO2 forms an order of magnitude faster than Cu
Keywords: Laser treatment; Oxidation; Crystallization; X-ray diffraction; Metallic glasses